(-2)+5:6
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


Lời giải chi tiết:
6 – 5 – 1 = 0 | 6 – 4 – 2 = 0 | 6 – 3 – 3 = 0 |
6 – 1 – 5 = 0 | 6 – 2 – 4 = 0 | 6 – 6 = 0 |

5 +1 = 6 4 + 2 = 6 3 + 3 = 6
6 - 5 = 1 6 - 2 = 4 6 - 3 = 3
6 - 1 = 5 6 - 4 = 2 6 - 6 = 0
5 +1 = 6 4 + 2 = 6 3 + 3 =6
6 - 5 =1 6 - 2 =4 6 - 3 =2
6 - 1 = 5 6 - 4 = 2 6 - 6 =0

a: \(=\dfrac{4}{5}+\dfrac{1}{5}\cdot\dfrac{5}{2}=\dfrac{4}{5}+\dfrac{1}{2}=\dfrac{8}{10}+\dfrac{5}{10}=\dfrac{13}{10}\)
b: \(=\dfrac{5}{6}\cdot\dfrac{1}{5}\cdot\dfrac{2}{5}=\dfrac{1}{6}\cdot\dfrac{2}{5}=\dfrac{2}{30}=\dfrac{1}{15}\)

Bài 2:
a: 2/6x5/3=10/18=5/9
b: 11/9x5/10=55/90=11/18
c: 3/9x6/8=1/3x3/4=1/4
d: 4/9x12/16=48/144=1/3
e: 25/15x6/7=5/3x6/7=30/21=10/7
f: 6/10x15/20=90/200=9/20
Bài 1
4/5 x 6/7= 24/35
2/9 x 1/2= 2/18= 1/9
1/2 x 8/3= 8/6= 4/3
7/9 x 6/5= 42/45= 14/15
8/7 x 5/9= 40/63
10/11 x 22/15= 220/165= 4/3
Bài 2
2/6 x 5/3= 1/3 x 5/3=5/9
11/9 x 5/10= 11/9 x 1/2= 11/18
3/9 x 6/8= 1/3 x 3/4 =3/12= 1/4
4/9 x 12/16= 4/9 x 3/4= 12/36= 1/3
25/15 x 6/7= 5/3 x 6/7= 30/21= 10/7
6/10 x 15/20= 3/5 x 3/4= 9/20

Lời giải:
1.
$3\frac{1}{4}-2\frac{1}{3}=3+\frac{1}{4}-(2+\frac{1}{3})$
$=3-2+\frac{1}{4}-\frac{1}{3}$
$=1+\frac{1}{4}-\frac{1}{3}=\frac{5}{4}-\frac{1}{3}=\frac{11}{12}$
2.
$6\frac{5}{9}+2\frac{5}{6}=6+\frac{5}{9}+2+\frac{5}{6}=8+\frac{5}{6}+\frac{5}{9}=8+\frac{25}{18}=8+1+\frac{7}{18}=9+\frac{7}{18}=9\frac{7}{18}$
3.
$6\frac{5}{9}-2\frac{5}{6}=6+\frac{5}{9}-(2+\frac{5}{6})$
$=6+\frac{5}{9}-2-\frac{5}{6}$
$=(6-2)+\frac{5}{9}-\frac{5}{6}$
$=4+\frac{5}{9}-\frac{5}{6}=\frac{41}{9}-\frac{5}{6}=\frac{67}{8}$

\(=\sqrt{\dfrac{\left(5-2\sqrt{6}\right)^2}{25-24}+\sqrt{\left(3-\sqrt{6}\right)^2}}=\sqrt{25+24-20\sqrt{6}+3-\sqrt{6}}=\sqrt{52-21\sqrt{6}}\)

\(=\dfrac{2}{35}\cdot\dfrac{5}{6}\cdot7+\dfrac{5}{2}\cdot\dfrac{7}{6}\cdot\dfrac{8}{9}\cdot\dfrac{7}{2}=\dfrac{1}{3}+\dfrac{245}{27}=\dfrac{245+9}{27}=\dfrac{254}{27}\)

6 x 2 =12
3 x 6 = 18
6 x 5 = 30
2 x 6 = 12
6 x 3 = 18
5 x 6 = 30
(-2) + 5 : 6
= - 2 + \(\frac56\)
= - \(\frac{12}{6}\) + \(\frac56\)
=- \(\frac{7}{12}\)
(-2) + 5 : 6
= - 2 + \(\frac{5}{6}\)= - \(\frac{12}{6}\) + \(\frac{5}{6}\)=- \(\frac{7}{12}\)